Chemical constituents and pharmacological profile of Gunnera manicata L. extracts (Brazilian Journal of Pharmaceutical Sciences, 2014)
Gunnera perpensa L. (Gunneraceae) is a native South African plant widely used in traditional medicine as an antibacterial and antifungal. In southern Brazil there is the native species called Gunnera manicata L. that also belongs to the Gunneraceae. Nevertheless, there is no information about chemical and pharmacological properties of South American Gunnera species. Therefore this study aimed at assessing the phytochemical and pharmacological profiles of aqueous and methanol Brazilian G. manicata extracts. The results showed that antimicrobial activity in an agar diffusion assay was effective against Staphylococcus aureus and Candida albicans . Phenolic compounds were investigated by liquid chromatography coupled with a tandem mass spectrometer (LC-MS/MS) and all extracts presented gallic acid and only the methanol extract obtained from the leaves exhibited hyperoside. Rutin, quercetin and chlorogenic acid were not found in the samples analysed. Total phenolic content was higher in methanol extract and total flavonoid content was low in all extracts. Antioxidant activity was evaluated by the 2,2-diphenyl-1-picryl-hydrazyl (DPPH) radical test, and all samples presented good to moderate antioxidant activity. These results encourage complementary studies on the chemical composition of the plant extracts focusing on isolation and structure elucidation of their active compounds.